The Use of ICT In English Learning: Students’ Perceptions and Expectations - Bansa, Yorina (English Language, Linguistics, Literature, And Education Journal, 2023)
Since the technology development educators should consider this to be a value for educational purposes. This study attempts to investigate the students’ perceptions and students’ expectations on the use of ICT in English learning. The writer sees a need to carry out this study as it provides a platform to discover pedagogical implications that would benefit the Y-generation in terms of using ICTs as media in their English learning. The respondents of this research comprise 20-second year students completing their bachelor’s degree in English literature faculty, The State Institute for Islamic Studies (IAIN) Sultan Thaha Syaifuddin Jambi, Sumatra, Indonesia. The students’ perceptions and students’ expectations were measured through a questionnaire. The questionnaire aims to find out about college students’ perception and expectations of computer technology use in English learning. There are three parts of questionnaire; Part one found present English learning and teaching situation in their institute and divided into computer facilities in their institutes, present their English learning situation, and students use of ICT in their daily life. Part two found students’ perceptions of the use of ICT in English learning, and Part three found students’ expectations of the use of ICT in English learning. The findings showed that respondents agree that ICT is useful for English learning especially for the item ‘computer can serve as tools for learning purposes’. And respondents generally agree to the statements which lead to the point that ICT can be expected to help respondents’ in English learning especially for the item ‘I need teachers/experienced people to teach me how to use online learning resources’, ‘I hope computers can be used to provide more interactive activities for students’, and ‘I hope the use of ICT will help me to learn English more efficiently’. The results of this study may be beneficial to EFL educators in incorporating ICT into their teaching repertoire.